An efficient heterogeneous ligand free C–N coupling reaction catalyzed by palladium supported on magnetic nanoparticles. Issue 2 (13th January 2016) - Rafiee, Ezzat; Ataei, Ali; Joshaghani, Mohammad
Graphical abstract: Abstract: The catalytic activity of palladium supported on magnetic nanoparticles in the amination coupling reaction of different nitrogen containing substrates with aryl halides was investigated. C–N bond formation was achieved in moderate to excellent yields and the catalyst could be separated by magnetic decantation.